16th UC Berkeley Heavy Held at Red Lion Inn-Sacramento - Watkins, Howard::::::::: (1984)
David Atkinson, Joe Barkett, Kirk Wilson and Frank Gumpert wearing swimsuits sitting in in-suite jacuzzi David and Joe doing toast